(untitled) (Research, Society and Development, 2020)
The food industry has increasingly sought for native and modified starches from alternative sources for different purposes, either to modify the texture or to add functional value to food. Irradiation applied to starches can induce emulsifying power, reduce retrogradation and improve texture, among other changes. The goal of this work was to evaluate the technological application of irradiated saffron starch (Curcuma longa L.) submitted to different radiation doses (0, 2.5, 5, 7.5 and 10 kGy) in carrot cake. The analyzes performed on the cakes were moisture, protein, lipids, ash, carbohydrates, specific volume, instrumental color of the crust and crumb, texture profile, microbiological analysis and sensory analysis of acceptance, purchase intention and acceptability index. The quality standard of the cakes was in accordance with the legislation. The radiation doses influenced only the protein and ash content and the color of the crust and the crumb of the cakes. The acceptability rate for the cakes was higher than 80%, indicating that the partial replacement of the wheat is viable.